An Achievement Test in Mathematics in the Modern World Course: The Standardization Process - Baybayan, Jericho Y.; Lacia, Michelle R. (Future Science / FSH-PH Publications, 2024)
This study aimed to construct and standardize an achievement test in Mathematics in the Modern World (MMW) course. Achievement test evaluates a student’s performance after a given period of instruction. Using the instrumentation research design, the data were gathered among 273 tertiary students of Notre Dame University enrolled during the second semester of Academic Year 2020-2021. Among these, 38 pilot tested and 213 tested the reliability of the instrument. This study further utilized the following: a 4-point Likert scale for the validation of the instrument, difficulty value and discrimination index formulas for the analysis of each item, and KR20 reliability for internal consistency. Furthermore, a test manual for the MMW achievement test was also established. The preliminary total number of Items before MMW teachers’ validation was 42 items covering the topics for the first 12 hours of the MMW Syllabus. These items were validated through Aiken’s Item Validity method which resulted in the acceptance of 42 items. After rigorous processes, it resulted in the acceptance of 34 items for the MMW achievement test. The instrument’s average validity is 0.935, and the reliability is 0.701 which means that this tool has high validity and acceptable reliability.